Panorama, estimativa e avaliação do potencial de produção e utilização do biogás de reatores UASB em ETEs operadas pela Companhia de Água e Esgoto do Ceará - Araújo, Anderson Barbosa (2019)
This study aimed to assessand evaluate the energy reuse potential of biogas from UASB reactors in sewage treatment plants (STP) operated by CAGECE. A STPinventory concerning the units in Ceara was done in order to quantify itsplants by their adopted technologies, to classify them with regard to their population size and wastewaterflow rate, and to estimate the efficiency of STPswith UASB reactors.CAGECEprovided institutional Excel spreadsheets to be consulted along with the online National Water Agency database.A big range of updated scientific literature was also consulted in order to gather information about electric and thermic energy consumptionrates, as well as COD and biogas production indexes. The obtained results, after a thorough statistical analysis and purge of outliers, using Excel, were then represented in graphics, tables and charts. Hence, although there has been noticed a numerical superiority of micro and small STPs using septic tank, it was also possible to realize a greatfeasibilityin regards of reusing biogas from STP with UASB reactors to produce thermic energy and feed appropriate stoves in order to cook food. During the STP UASB reactor efficiency analyses, the majority of the STP was placed in the worst scenario (WS) and typical scenario (TS) categories, and it was easy to notice that those STPsof which technological route contemplated some kind of effluent post-treatment processalsopresented a higher capacity of removing COD than the ones without a post-treatment unit.Concerning the projected scenario by the 2014 BSMP and the proposed alternative, there was a large carbon creditsgeneration and a tremendousproduction of electricity which was enough not only to supply the STPs internal demands, but also to produceenergy credits with the state energy utility, providing profits to the state water and wastewater utility. Finally, the economic studyperformed for the alternative proposal returned CAPEX and OPEX values that permitted a short-time pay-back of these investments, which did not happen to the 2014 BSMP projected scenario.